Analysis of The Wisdom of Tasyrī'-Legal Verses Claimed to Be Gender Biased In Indonesia’s Official Tafsir Literature - Hadi, Sutrisno; Tiswarni, Tiswarni; Ariani, Dina; Hafizh, Muhammad (AL QUDS : Jurnal Studi Alquran dan Hadis, 2024)
The issues of gender and women’s rights have permeated into the Quran.  Some advocates for gender equality argue that the Quran is a source of perpetuating the oppression of women.  This is due to their perception of certain Quranic verses that are claimed to have a gender bias.  However, it is widely understood in the Islamic worldview that the Quran is a sacred book and contains principles of justice for all His creations, regardless of gender.  Therefore, this article aims to examine the wisdom of tasyrī’ in the verses that are alleged to have a gender bias from the perspective of the Ministry of Religious Affairs of the Republic of Indonesia’s Tafsir named Al-Qur’an dan Tafsirnya; Edisi yang Disempurnakan.  The focus will be on four main topics: polygamy, interfaith marriage, inheritance distribution, and the testimony of women.  This work is a literature review that explores the explanation of the Ministry of Religious Affairs of the Republic of Indonesia.  This research demonstrates that the interpretation provided by the Ministry of Religious Affairs of the Republic of Indonesia contains logical and argumentative explanations regarding the wisdom of tasyrī’ from the verses related to the four gender-biased topics claimed.  Various tasyrī’ wisdoms further confirm that there is a benefit for both Muslim men and women behind the establishment of these four sharia rules.  Therefore, the claims made by feminist followers that these verses discredit and degrade the dignity of women are not accurate.